Public Policies, Capital Availability and Firms’ Internationalization in Latin America: The cases of Argentina, Brazil and Chile - Finchelstein, Diego (2012)
In the last years the internationalization of firms from developing countries has started gaining increased attention. This research attempts to contribute to the study of the process of firms’ internationalization by analyzing three Latin-American countries and connecting this phenomenon with capital availability and state actions to promote capital. Both direct and indirect policies have been used to encourage capital availability. Brazil is the country in which the state has intervened more actively and directly to increase capital availability and it is the most successful case in terms of firms’ internationalization. Chile also obtained a favorable outcome by using indirect policies to strengthen the capital market. Argentina lacks a consistent set of policies and, as a result, had a relatively poor performance in the internationalization of its firms.